2007
DOI: 10.1248/cpb.55.87
|View full text |Cite
|
Sign up to set email alerts
|

Compressed Oxygen in Drug Stability Experiments

Abstract: A drug stability experiment accelerated by compressed oxygen was established. The stability of 10% ascorbic acid solution as a model was studied and the kinetic parameters were obtained with the newly established experimental method. Because ascorbic acid degrades under both anaerobic and aerobic conditions, the total rate constant k total can be expressed as: k total ‫؍‬k anaerobic ؉k aerobic , where k anaerobic and k aerobic are the rate constants of anaerobic and aerobic degradations, respectively. The k an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 24 publications
0
9
0
2
Order By: Relevance
“…The relationship between k aerobic and oxygen pressure was expressed as Eq. (6) by Shi et al 13) k aerobic =A aerobic exp…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The relationship between k aerobic and oxygen pressure was expressed as Eq. (6) by Shi et al 13) k aerobic =A aerobic exp…”
Section: Resultsmentioning
confidence: 99%
“…Many papers reported that some drugs are unstable (or stable) under aerobic (or anaerobic) conditions, 1 11) but few reported the oxidation rate. 12,13) Captopril (I), an orally active inhibitor of the angiotensin-converting enzyme, is used widely to treat hypertension and congestive heart failure. Like all thiols, captopril is subjected to oxidation to form the dimer 14,15) captopril disulˆde (II).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existují různé mechanismy degradace kyseliny askorbové, rozdíl-né pro aerobní, nebo anaerobní podmínky (Shi a Zhan 2007). Prů-běh degradace askorbové kyseliny závisí na druhu vody a může při ní vznikat peroxid vodíku, přičemž se mohou tvořit různé degradační produkty.…”
Section: Vliv Redukujících Látek Na Rychlost Redukce Vzdušného Kyslíkunclassified
“…Askorbová kyselina se může rozkládat aerobním i anaerobním způsobem, pokaždé za tvorby jiných produktů, např. diketogulonové kyseliny nebo furfuralu (Shi a Zhan 2007).…”
Section: After 10 Min Heating At 121 °C Vliv Redukujících Látek Na Ryunclassified